Peningkatan Kemampuan Berhitung Anak Melalui Permainan Grafik Survei di Taman Kanak-Kanak - Dedet, Dedet; Yulsyofriend, Yulsyofriend (Penerbit Aksara Rentaka Siar (ARS), 2020)
The purpose of this study was to determine the increase in children's numeracy skills through the media of survey charts. This type of research is a classroom action research (CAR) that uses qualitative and quantitative approaches. The subjects of this study were the teacher and children of B1 Aisyiyah kindergarten with a total of 15 people. The results showed an increase in children's numeracy skills through the media survey game graphics had increased. The percentage of completeness of learning cycle I was only 32%, then in cycle II an increase in children's numeracy skills through the media of survey graphs was equal to 87%